Kognitariat: Eksploitasi Kelas Pekerja Kognitif dalam Era Ekonomi Pengetahuan - Hudha, Choirul; Salim, Permata Mohamad (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Abstract: The development of technology in post-industrial society creates a knowledge economic system, with production that is not only based on things but also intensive knowledge. The workers who rely on knowledge and skills for the centre of their activities in the knowledge economy are called cognitive workers. The cognitive workers in the knowledge economy era just paid little attention to their rights and obligations. That’s why they get unfair and fewer benefits during work and often get exploited and disadvantaged when they work. The cognitive workers who have the exploitation are called cognitariat. Therefore, this research is new, empirically and theoretically. It is about the exploitation experienced by cognitive workers. Researchers used literature studies obtained through the University of Indonesia library software (remote-lib.ui.ac.id), and search engines such as Google Scholar, Science Direct (Elsevier), JSTOR, Web of Science, and other journal directories by open access with the keyword, “cognitive worker”, “knowledge-based economy”, “exploitation in cognitive labour”, “labour in knowledge era” and “cognitariat”. The results of the research reveal that exploitation of cognitive workers because of the responsibility of work and overstepping working. Thus, the exploitations is not only based on a material, like the proletariat., but also at a supra structural basis, that’s knowledge on the cognitariat.